The number is -9
Step-by-step explanation:
Let x be the number then according to given statement
![4x+10 = x-17](https://tex.z-dn.net/?f=4x%2B10%20%3D%20x-17)
Subtracting 10 from both sides
![4x+10-10 = x-17-10\\4x = x-27](https://tex.z-dn.net/?f=4x%2B10-10%20%3D%20x-17-10%5C%5C4x%20%3D%20x-27)
Subtracting x from both sides
![4x-x = x-x-27\\3x = -27](https://tex.z-dn.net/?f=4x-x%20%3D%20x-x-27%5C%5C3x%20%3D%20-27)
Dividing both sides by 3
![\frac{3x}{3} = \frac{-27}{3}\\ x = -9](https://tex.z-dn.net/?f=%5Cfrac%7B3x%7D%7B3%7D%20%3D%20%5Cfrac%7B-27%7D%7B3%7D%5C%5C%20x%20%3D%20-9)
<u>Verification:</u>
![4(-9)+10 = -9-17\\-36+10=-26\\-26=-26](https://tex.z-dn.net/?f=4%28-9%29%2B10%20%3D%20-9-17%5C%5C-36%2B10%3D-26%5C%5C-26%3D-26)
The number is -9
Keywords: Linear equation, variables
Learn more about linear equation at:
#learnwithBrainly
Answer:
4 gigabytes
Step-by-step explanation:
Equation: 68.50=48+5x
Rearrange the polynomial:
a^2–2ab+b^2 - c^2
((a-b)(a-b))-c^2
(a-b)^2-c^2
Set x =a-b and y=c. The formula becomes
x^2-y^2
factoring this polynomial, we get
(x+y)(x-y)
Substituting back, we get:
(a+b+c)(a+b-c)
Let’s multiply it out to check:
A^2 -ab ac
- ab B^2 -bc
-ac bc -c^2